DIE KONINGSKAP VAN CHRISTUS EN DIE STAAT IN ‘N GODSDIENSTIG-PLURALISTIESE LAND - RESPONS: W P Esterhuyse, Departement Filosofie, Universiteit van Stellenbosch = THE KINGSHIP OF CHRIST AND THE STATE IN A RELIGIOUSLY PLURALISTIC COUNTRY - Jonker, W. D. (1984)
Referring to the argument that the granting of more political rights to the so-called Coloured and Asian population groups will jeopardize the Christian character of the South African state, as these groups include many adherent of non-Christian religions, the author examines the question whether the ideal of a Christian state must necessarily lead to such a conclusion. He contends that those who use this argument are probably influenced by a type of theocratic thinking of Dutch origin in which the corpus Christianum ideal still plays a large role. In doing so, they too easily identify the White South African society (or even Afrikanerdom) with Christianity, resulting in their defense of a form of political discrimination against these population groups on religious grounds. The author argues that the necessity to distinguish clearly between the character of the Church and state, makes this view untenable. He contends that the Christian character of the state cannot be upheld by discriminatory political measures.
Keywords: Apartheid; Christian character; Religiously Pluralistic country; South Africa